PENGEMBANGAN KURIKULUM PENDIDIKAN KRISTIANI - Picanussa, Branckly Egbert (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2019)
Some Christian education experts have expressed their views on how the church should develop a curriculum to educate church members to achieve maturity in the Christian faith. This article purpose to develop a curriculum for Christian education in Church ministry. The method used is a literature study on the opinions of D. CampbellWyckoff and Maria Harris. The characteristics of Wyckoff and Harris's opinions and various responses in